The Money Market Mutual Fund Liquidity Facility - Kenechukwu Anadu; Marco Cipriani; Ryan M. Craver; Gabriele La Spada (Federal Reserve Bank of New York, 2021)
In this article, we discuss the run on prime money market funds (MMFs) that occurred in March 2020, at the onset of the COVID-19 pandemic, and describe the Money Market Mutual Fund Liquidity Facility (MMLF), which the Federal Reserve established in response to it. We show that the MMLF, like a similarly structured Federal Reserve facility established during the 2008 financial crisis, was an important tool in stemming investor outflows from MMFs and restoring calm in short-term funding markets. The usage of the facility was higher by funds that suffered larger outflows. After the facility's introduction, outflows from prime MMFs decreased more for those funds that had a larger share of illiquid securities. Importantly, following the introduction of the MMLF, interest rates on MMLF-ineligible securities decreased at a slower rate than those on MMLF-eligible securities, even after controlling for credit risk.
Keywords: G23; G28; G11; 330; COVID-19; money market funds; runs; Federal Reserve lending facilities